Love from your friend, Hannah : a novel - Skolsky, Mindy Warshaw (New York, N.Y. : DK Ink Book, 1998)
From her home in back of the Grand View Restaurant in rural New York, Hannah writes letters to her best friend, a pen pal, and even to President and Mrs. Roosevelt.
"A Richard Jackson book."
Includes bibliographical references.
780
Accelerated Reader AR
Keywords: Letters -- Fiction; Pen pals -- Fiction; United States -- History -- 1933-1945 -- Fiction